2008
DOI: 10.1002/hep.22064
|View full text |Cite
|
Sign up to set email alerts
|

Leptin's mitogenic effect in human liver cancer cells requires induction of both methionine adenosyltransferase 2A and 2β

Abstract: Leptin is an adiopokine that plays a pivotal role in the progression of liver fibrogenesis and carcinogenesis. Recently, leptin was shown to be mitogenic in human liver cancer cell lines HepG2 and Huh7. Whether leptin can act as a mitogen in normal hepatocytes is unclear. Methionine adenosyltransferase (MAT) is an essential enzyme that catalyzes the formation of S-adenosylmethionine (SAMe), the principal methyl donor and precursor of polyamines. Two genes (MAT1A and MAT2A) encode for the catalytic subunit of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 75 publications
(134 citation statements)
references
References 32 publications
7
127
0
Order By: Relevance
“…Due to its mitogen effect, a condition of hyperleptinemia could favour the development of malignancies. In close agreement with this hypothesis, several lines of evidence support the role of leptin in the neoplastic processes [6][7][8][9]. Moreover, this is further supported by some genetic evidences showing a correlation between serum leptin levels, leptin receptor polymorphisms, and the risk of breast cancer [10,11].…”
supporting
confidence: 55%
“…Due to its mitogen effect, a condition of hyperleptinemia could favour the development of malignancies. In close agreement with this hypothesis, several lines of evidence support the role of leptin in the neoplastic processes [6][7][8][9]. Moreover, this is further supported by some genetic evidences showing a correlation between serum leptin levels, leptin receptor polymorphisms, and the risk of breast cancer [10,11].…”
supporting
confidence: 55%
“…We supposed that it might be related to cellular stress brought on by LV-shMAT2B, bcl-x L was able to induce apoptosis in response to cellular stress [30] . We found that LV-shMAT2B prevented proliferation in HepG2 cells, Leptin could induce proliferation in human hepatocarcinoma cells by up-regulating cyclin D1 [31] but Komal [30] found that Leptin could increase SAMe levels adipokine shown to be mitogenic in human liver cancer cell lines HepG2 and Huh7, and its mitogenic effect was also related with the expression of MAT2B.…”
Section: Discussionmentioning
confidence: 99%
“…MAT2␤ expression is induced in cirrhosis and hepatocellular carcinoma (HCC). Importantly, increased MAT2A and MAT2␤ expression offer liver cancer cells a growth advantage (2,3).…”
Section: Methionine Adenosyltransferase (Mat)mentioning
confidence: 99%